2005
DOI: 10.1002/ejoc.200500150
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective C‐Silylation of Fatty Acid Methyl Esters

Abstract: New silylated saturated and unsaturated fatty acid methyl esters (FAMEs) possessing a hydrophobic frame and a hydrophilic core were prepared. C‐silylations of the ester group were achieved either by treating FAMEs with various alkyl‐ and chlorosilyl triflates or by subjecting various chlorosilanes to reaction with the corresponding FAME lithium enolates. Both routes led to the exclusive formation of one isomer identified as the C‐silylated form on the basis of the analytical results. (© Wiley‐VCH Verlag GmbH &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Although the two O-and C-silyl forms are obtained in the case of organic esters (Emde and Simchen, 1977;Emde et al, 1982;Simchen, 1991), silylation of FAME (methyl undecanoate, methyl palmitate, methyl oleate and methyl linoleate) leads exclusively to one isomer: the C-silylated derivative. The origin of this higher selectivity lies in the fact that, surprisingly, silyltriflate catalyzes the isomerization of O-silyl forms to C-silyl forms as already demonstrated by using O-silyl form as initial reactant (El Kadib et al, 2005a) (Scheme 1).…”
Section: Silylation In α-Position Of Triglyceryl Groupmentioning
confidence: 85%
See 2 more Smart Citations
“…Although the two O-and C-silyl forms are obtained in the case of organic esters (Emde and Simchen, 1977;Emde et al, 1982;Simchen, 1991), silylation of FAME (methyl undecanoate, methyl palmitate, methyl oleate and methyl linoleate) leads exclusively to one isomer: the C-silylated derivative. The origin of this higher selectivity lies in the fact that, surprisingly, silyltriflate catalyzes the isomerization of O-silyl forms to C-silyl forms as already demonstrated by using O-silyl form as initial reactant (El Kadib et al, 2005a) (Scheme 1).…”
Section: Silylation In α-Position Of Triglyceryl Groupmentioning
confidence: 85%
“…Among the methylene groups, the one located in ␣-position to a carboxy function possesses higher reactivity, which was usually exploited in halogenations, sulfonations, Guerbet's reaction and Claisen condensation (Biermann et al, 2000). Recently, we described a selective ␣-silylation of FAME by using various silyltriflate (El Kadib et al, 2005a). Although the two O-and C-silyl forms are obtained in the case of organic esters (Emde and Simchen, 1977;Emde et al, 1982;Simchen, 1991), silylation of FAME (methyl undecanoate, methyl palmitate, methyl oleate and methyl linoleate) leads exclusively to one isomer: the C-silylated derivative.…”
Section: Silylation In α-Position Of Triglyceryl Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopic data indicated that germanium hydride had added to the C C bond without interaction between the germanium center and the carbonyl group. The reaction is regiospecific and only the anti-Markovnikov product was obtained because no 13 C NMR signal corresponding to CH 3 -CH(GePh 3 )-CH 2 was observed.…”
Section: Hydrogermylation Of Methyl 10-undecenoatementioning
confidence: 98%
“…[145] wurden in 19-75 % Ausbeute durch Umsetzung der Fettsäu-reester mit Alkylsilyltriflaten und Triethylamin oder durch Reaktion der Lithiumenolate mit Chlorsilanen gewonnen. [149] Methylverzweigte Oleate, die als Schmierstoffe von Interesse sind, ließen sich durch allylische Bromierung mit N-Bromsuccinimid und Reaktion der Bromide mit Organocupraten herstellen. [150] Die allylische C-H-Bindung in ölsäurereichem Sonnenblumenöl wurde auch genutzt, um reaktive a,b-ungesättigte Ketone durch Photooxidation mit Singulett-Sauerstoff zu erhalten.…”
Section: C-h-aktivierungunclassified